병원선택 요인이 고객만족과 재이용의도에 미치는 영향 - 박광민(Kwang-Min Park); 양종현(Jong-Hyun Yang); 장동민(Dong-Min Chang) (한국콘텐츠학회 논문지, 15(8), 2015)
This study verified empirically and analyzed systematically how the hospital choice factors of visitors in general hospitals influence customer satisfaction and revisiting intention. As a survey way for hypothesis verification of this study, we took a direct survey for 4 weeks(June 1 to June 28, 2014) to the outpatients and their guardians visiting the three general hospitals in Busan, Ulsan, Gyeong-nam. For the survey we distributed a total of 550 questionnaire and used the final 519 of them in verifying this research model except unreliable 31 data. The result showed that human element, accessibility element and public image of hospital choice factors effected on the customer satisfaction, but physical and effectiveness factors did not effect on it. And, the only public image factor of hospital choice factors have a good effect on the revisiting intention. Also, it influenced between customer satisfaction and revisiting intention, so it is proved that the customer satisfaction is a important factor to revisiting intention. The hospitals should promote a hospital policy to connect with customer satisfaction and income growth and provide a high-quality medical service by making effectively use of planning priority strategies of hospital management with a variety of factors. 본 연구는 병원 이용자의 병원선택요인이 고객만족과 재이용의도에 미치는 영향을 체계적으로 분석하기 위한 목적으로 수행하였다. 가설 검증을 위해 부산, 울산, 경남지역 3개 종합병원을 이용한 외래환자 및 보호자를 대상으로 2014년 6월 1일부터 6월 28일까지 4주간 직접 설문조사를 통해 519부의 자료를 수집하였다. 주요 연구결과는 다음과 같다. 병원선택요인 중 인적요인, 접근성요인, 대외이미지요인은 고객만족에 영향을 미치는 것으로 나타났으나, 물리적요인, 효율성요인은 고객만족에 유의한 영향을 미치지 않는 것으로 분석되었다. 그리고 병원선택요인 중 대외이미지요인이 재이용의도에 유의한 영향을 보였으며, 고객만족 또한 재이용의도에 유의한 영향을 미치는 것으로 나타났다. 본 연구 결과를 통해, 병원경영진이 환자만족도와 재이용의도를 높여 궁극적으로 수익성의 제고로 연결시키기 위해서는 경영전략의 수립 시 병원선택에 영향을 미치는 다양한 요인들의 역학관계를 고려하는 것이 매우 중요함을 시사해 주고 있다.